Functional implications of tissue factor localization to cell-cell contacts in myocardium. - Luther, T; Dittert, D; Kotzsch, M; Erlich, J; Albrecht, S; Mackman, N; Müller, M (2000)
Recently published studies suggest that the procoagulant receptor protein tissue factor (TF) is involved in vitro in cell adhesion and migration, via an interaction of its cytoplasmic domain with cytoskeletal proteins. Interestingly, TF is abundantly expressed in myocardium, but not in skeletal muscle. To elucidate the possible roles of TF in the myocardium, this study examined the cellular distribution of TF in relation to cytoskeletal proteins, as well as its relative amounts in different segments of premature, mature, and pathologically altered cardiac muscle. In juvenile and adult hearts, TF was predominantly detectable in the transverse part of the intercalated discs, where it co-localized with cytoskeletal proteins such as desmin and vinculin. The lowest amount of TF was observed in right atrial and the highest in left ventricular myocardium, which correlated with the number of contact sites of cardiomyocytes in these segments of the cardiac muscle. Lower levels of TF were present in structurally altered myocardium from patients with hypertension or ventricular hypertrophy. In addition, TF expression was decreased in human heart during sepsis and transiently decreased in rabbit heart in an endotoxaemia model, which indicates that a reduction in TF may contribute to cardiac failure in sepsis. The microtopography of TF at cardiomyocyte contact sites indicates that TF may play a structural role in the maintenance of cardiac muscle.